The influence of the politicians on macroeconomic performance: An analysis of donald trump’s tweets - Silahtaroğlu, Gökhan; Dinçer, Hasan; Yüksel, Serhat (Springer Science and Business Media Deutschland GmbH, 2021)
The aim of this study is to understand the role of the politicians on the macroeconomic situation of the countries. For this purpose, the tweets of Donald Trump are taken into consideration. Text mining approach is used to evaluate these tweets and most used words are identified. Next, all-important keywords are matched with significant topics and 4 different classes are identified for this condition, which are financial, social, military, and political issues. After that, these keywords are ranked with the help of fuzzy VIKOR approach according to their impacts on macroeconomic performance. In this context, five different factors are also defined, which represent macroeconomic performance that are economic growth, unemployment, inflation, international trade, and industrial development. The findings show that political and economic factors are the most important items which affect macroeconomic situation of the country. It is recommended that politicians should not make negative explanations about political and financial conditions in order not to have unfavorable results in the economic activities.
Keywords: Fuzzy VIKOR; Politic Intervention; Stock Exchanges; Text Mining